OPTIMIZATION OF OVULATION INDUCTION IN INFERTILE WOMEN WITH ENDOCRINE INFERTILITY - Kurbaniyazova Madina Zafarzhanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Today, the diagnosis of polycystic ovary syndrome is based on the provisions of the Rotterdam Convention (2003) and includes, first of all, the diagnosis of hyperandrogenism and oligo/anovulation, which do not allow reproductive function. Other manifestations of PCOS, associated with insulin resistance and dyslipidemia, continue to be widely discussed in the literature. And since the incidence of infertility in women with hyperandrogenism and anovulation reaches 90%, the issues of treatment of such patients are extremely relevant and require a comprehensive solution. This article is devoted to the treatment of anovulation by administering ovulation inducers. Research in the field of reproductive gynecology served as the basis for the synthesis and clinical use of drugs that stimulate ovulation, and thereby make it possible to realize reproductive function.